Training for Social Entrepreneurship: An Emerging Agenda in Higher Education Institutions in Mexico - Gómez Díaz, María del Rocío (2022)
In Mexico, poverty rates reach more than half of the population. A high percentage of the jobs created requires only basic studies, which accentuates unemployment for people with higher education. Hence, a large number of professionals fail to enter the labor market. Thus, the objective of this research is to identify strategies and actions that the State and public institutions of higher education must implement to strengthen the ecosystem and the formation of human capital for social entrepreneurship. The methodology consisted of a review of specialized literature on business and social entrepreneurs to identify their main characteristics and differential elements. This means, the present research is a multidimensional and multisectoral analysis of the ecosystem for entrepreneurship in Mexico and an exploration of the training of social entrepreneurs in Higher Education Institutions. Similarly, according to results, the ecosystem needs a greater connection between its actors and financial support. Likewise, professional preparation requires considering personality, academic, and research aspects. Moreover, conclusions highlight emerging needs required to develop an ecosystem that enables strategic alliances and provides those seeking to undertake, advice and venture capital financing for the creation of social enterprises.